Pelatihan Sholawat Albanjari Sebagai Wadah Kreativitas Anak Anak Di Desa Jambangan : Pelatihan Sholawat Al-Banjari Sebagai Strategi Pengembangan Kreativitas Anak Dalam Konteks Seni Islam Di Desa Jambangan - Mochammad Busyro Nurul Furqon; Solchan Ghozali (Journal of Research and Community Service, 2025)
The Al-Banjari sholawat training program in Jambangan Village represents a strategic initiative aimed at developing children's creativity through the medium of Islamic arts. This study seeks to analyze the implementation of the Al-Banjari training, its impact on children's creative growth, and the challenges encountered during its execution. A Participatory Action Research (PAR) approach was employed, involving children aged 7–15 in planning, training, and evaluation processes. Data were collected through participatory observation, activity documentation, and pre- and post-training response assessments. The findings indicate a significant improvement in musical creativity, vocal expression, and artistic performance among the participants. The average engagement score increased from 2.37 to 4.66 following the training sessions. Furthermore, the program fostered stronger Islamic values, self-confidence, and a sense of collective spirit among the youth. Key challenges included limited facilities and the need for professional mentors, highlighting the importance of sustained support from the community and local government. This study demonstrates that Al-Banjari sholawat training serves not only as a means of preserving local Islamic cultural heritage but also as an effective tool for nurturing children's creativity and character. The findings underscore the importance of integrating religious art into community-based non-formal education programs, particularly in rural settings.